Decline in Estrogen Levels and Its Impact on Muscle Strength in Elderly Women: A Systematic Review - Cahyaningrum, Hapsari; Silanurrahmi, Athaya Zuhra; Hakim , Gamadhan Kholid Rahman (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: In the musculoskeletal system, old age is closely related to a decline in muscle strength. Decreased muscle strength in women is caused by the influence of changes in estrogen hormone levels. Several studies were conducted to see how estrogen affects muscle mass, muscle function, muscle damage, muscle regeneration, inflammation in the body, mitochondrial funct¬ion, and substrate metabolism. Therefore, the study was carried out with the aim of conducting further study focusing on estrogen on muscle strength in elderly women.Subjects and Method: The study was conducted with a systematic review design. The study was carried out in accordance using PRISM guidelines with the PICO formula. Population: elderly women, Intervention: estrogen hormone, Outcome: muscle weakness. Article searches were carried out through several databases, namely PubMed, Cochrane Library, Scopus Database, and Physio-therapy Evidence Database (PEDro) with the keywords: estrogen OR